القصور والبيوت المملوكية في القاهرة: دراسة أثرية وحضارية : [Mamluk Palaces and Houses in Cairo: An Archaeological and Civilizational Study] - Yaghi, Ghazwan, (Middle East and Islamic Studies E-Books Online, Collection 2021, ISBN: 9789004441286., 2021)
Mamluk Palaces and Houses in Cairo studies the types of extant residential buildings in Cairo from the Mamluk era (1250-1517 C.E.) and the factors affecting their design, architectural and decorative elements, and building materials. It provides an archaeological, architectural, historical, and documentary study of all the surviving palaces and houses, focussing on the structural and architectural status of its various parts. The author also discusses its present-day restoration and rehabilitation projects. In this book, Ghazwan Yaghi presents a variety of empirical material that sheds more light on the social and economic history of the Mamluk era, as well as a glossary of archaeological and documentary terminology that could serve as a tool for further research in Islamic architecture. القصور والبيوت المملوكية في القاهرة يدرس أنواع المباني السكنية الموجودة في القاهرة من العصر المملوكي (1250-1517 م) والعوامل المؤثرة في تصميمها، وعناصرها المعمارية والزخرفية، ومواد بناءها، إضافة لتقديم دراسة أثرية ومعمارية وتاريخية ووثائقية لكل القصور والبيوت الباقية، مع التركيز على الحالة الإنشائية والمعمارية لكافة أجزاءها، وملقية الضوء على مشاريع ترميمها وإعادة تأهيلها حتى الوقت الحالي. في هذا الكتاب، يقدم غزوان ياغي مادة ثرية تساهم في زيادة فهمنا للتاريخ الاجتماعي والاقتصادي للعصر المملوكي، كما يوفر مسرد المصطلحات الأثرية والوثائقية مادة علمية تزيد من فهمنا للعمارة السكنية الإسلامية التي يأتي المنتج المعماري فيها معبراً بصورة دقيقة عن أصحابه سواء منهم من أمر به أو من قام بتنفيذه.